2007
DOI: 10.1051/forest:2007015
|View full text |Cite
|
Sign up to set email alerts
|

Réponse germinative des graines de l’aulne glutineux et du bouleau pubescent à l’application d’acide gibbérellique et de traitements d’amorçage en combinaison avec du froid

Abstract: -The effects of seed moisture content (MC), gibberellic acid (GA 3 ) concentration, chilling and priming pretreatments on the germination of common alder (Alnus glutinosa) and downey birch (Betula pubescens) seeds were examined. After treatment, the seeds were allowed to germinate for 42 days at 15• C or 20. Treatment responses were similar at both temperatures and in both species. GA 3 treatment of seeds in fully imbibed (FI) state for 30 days, or at the lower, target moisture content (TMC) for 30−90 days, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…During winter, seeds are exposed to a moist-chilling condition resulting in a widening of the range of temperatures suitable for germination. The beneficial effect of moist pre-chilling on germination of Betula pendula is well documented (Atkinson 1992;Vanhatalo et al 1996;De Atrip and O'Reilly 2007;Tylkowski 2012). This study confirmed that a pre-chill improved the germination capacity and germination rate, and widened the thermal thresholds for germination in all provenances.…”
Section: Discussionmentioning
confidence: 99%
“…During winter, seeds are exposed to a moist-chilling condition resulting in a widening of the range of temperatures suitable for germination. The beneficial effect of moist pre-chilling on germination of Betula pendula is well documented (Atkinson 1992;Vanhatalo et al 1996;De Atrip and O'Reilly 2007;Tylkowski 2012). This study confirmed that a pre-chill improved the germination capacity and germination rate, and widened the thermal thresholds for germination in all provenances.…”
Section: Discussionmentioning
confidence: 99%
“…We established three treatments with different chilling duration: 15 days (T1), 30 days (T2) and 45 days (T3) and a control treatment, where seeds were not chilled (C). Chilling consisted of adjusting seeds to a moisture level of 33 % at 4 °C in darkness, conditions that have been reported to break dormancy while avoiding seed germination and deterioration ( De Atrip and O’Reilly 2007 ). Seed moisturizing was achieved by adding distilled water on seeds placed in 1.5ml microtubes ( Jones and Gosling 1994 ).…”
Section: Methodsmentioning
confidence: 99%
“…Wick and others (2008) recommended a 24-h water soak followed by a 60-d cold, moist stratification at 3 °C (37.4 °F). Because the seed in the present study originated from different locations but were collected, extracted, stored, stratified, and germinated in similar conditions as for past experiments, seed germination variability among the seed locations may have been attributable to a number of other factors including seed quality and maturity, weather conditions during seed maturation, and genetics (Atrip and O'Reilly 2007). In addition, Ann Smreciu (personal communication 2015) has observed and suggested that green alder seed will lose substantial viability without prompt extraction and cold storage.…”
Section: R E S U L T S a N D Discussion Length Of Cold-stratmentioning
confidence: 99%